PRAKTIKALITAS PERANGKAT EKSPERIMEN INDUKSI ELEKTROMAGNETIK ALTERNATIF SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Angga, Hendro; Zulirfan, Zulirfan; Sudrajad, Hendar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to examine the practicalities of product resulting from the research design and validation devices alternative electromagnetic induction experiment that has been done before. There are 15 students and 4 teachers from three senior high school in the city of Pekanbaru has been participated in this research. Data analyzed by using desciptif statistic. Data was collected by using the practicality questionnaire, interview protocol, and observation sheet. Based on the data analysis question form (questionnaire) obtained the value of the practicality of experimental device according to the teacher. Experimental tools and guides its use can help facilitate the teacher in the learning process of electromagnetic induction with the acquisition value of the practicality of the product is at high and very high category so device experiment practical used the teacher. From the results of question form (questionnaire) test the practicalities according to student, experimental device given ease in studying electromagnetic induction with the score on categories of high and very high. So the device experimental and guide book also practical used student. The practicality of experimental devices are supported by the results of the interviews and observations of research that given the same description that alternative electromagnetic induction experiment device can facilitate teacher and student in the learning process of electromagnetic induction.Key word : Practicality, alternative experiment device of electromagnetic induction.